Poéticas da deusa Durga/Kali na arte kathak e na cena contemporânea : Poetics of Goddess Durga/Kali in kathak art and in the contemporary scene - Ribeiro, Adriana Suely Queiroz, 1975- (2023)
Orientador: Mariana Baruco Machado Andraus